Intracellular Signaling Molecules Activated by Epstein-Barr Virus for Induction of Interferon Regulatory Factor 7 - Zhang, Luwen (American Society for Microbiology, 2001)
Epstein-Barr virus (EBV) latent membrane protein 1 (LMP-1) is the principal oncogenic protein in the EBV transformation process. LMP-1 induces the expression of interferon regulatory factor 7 (IRF-7) and activates IRF-7 protein by phosphorylation and nuclear translocation. LMP-1 is an integral membrane protein with two regions in its C terminus that initiate signaling processes, the C-terminal activator regions 1 (CTAR-1) and CTAR-2. Here, genetic analysis of LMP-1 has determined that the PXQXT motif that governs the interaction between LMP-1 CTAR-1 and tumor necrosis factor receptor-associated factors (TRAFs) is needed to induce the expression of IRF-7. Mutations in the PXQXT motif in CTAR-1 that disrupt the interaction between LMP-1 and TRAFs abolished the induction of IRF-7. Also, dominant-negative mutants of TRAFs inhibited the induction of IRF-7 by CTAR-1. The last three amino acids (YYD) of CTAR-2 are also important for the induction of IRF-7. When both PXQXT and YYD were mutated (LMP-DM), the LMP-1 mutant failed to induce IRF-7. Also, LMP-DM blocked the induction of IRF-7 by wild-type LMP-1. These data strongly suggest that both CTAR-1 and CTAR-2 of LMP-1 independently induce the expression of IRF-7. In addition, NF-κB is involved in the induction of IRF-7. A superrepressor of IκB (sr-IκB) could block the induction of IRF-7 by LMP-1, and overexpression of NF-κB (p65 plus p50) could induce the expression of IRF-7. In addition, we have found that human IRF-7 is a stable protein, and sodium butyrate, a modifier of chromatin structure, induces IRF-7.